Impact of ambulatory intravenous antibiotic therapy for children with pre-septal cellulitis. (26th December 2010) - Brugha, Rossa
Abstract : Aim: To assess the impact of ambulatory intravenous antibiotic therapy for children with preseptal cellulitis. Design: Retrospective audit of 62 patients presenting with preseptal cellulitis over a 12 month period. Setting: Paediatric Emergency Department, Chelsea and Westminster Hospital, London. Results: 62 patients identified from discharge summary coding. On review of medical notes 59 patients fulfilled criteria for preseptal cellulitis. Patients were attributed a modified severity score out of seven, based on signs and symptoms as previously1 19 patients (32%) were discharged home on oral antibiotics, one patient (2%) on topical therapy only, and 39 patients (66%) were started on intravenous antibiotics. There was a significant difference in symptom score between children started on oral versus intravenous antibiotic therapy (2.47 vs 3.21, p=0.021). Of the patients started on intravenous antibiotics, 22 children (56%) were managed on an ambulatory basis and 17 children (44%) were admitted. The management guideline allowed for ambulatory care, provided specified clinical factors were not present. The mean duration of antibiotic therapy was not different between the two groups (2.90 vs 2.75 days, p=0.79). Only three children in the study required imaging and there were no intracranial complications in either group. On a crude cost benefit analysis, the net fiscal benefit of a 3 day course of ambulatory versus inpatient intravenous therapy was calculated as £1672 per patient. For the study group, this represented a saving to the commissioning Trust of £36 784. Conclusions: In this study group, children requiring intravenous antibiotics for uncomplicated preseptal cellulitis were safely managed on an ambulatory basis. This conveyed a considerable financial benefit to the health economy, in addition to a reduction in the burden of hospitalisation placed upon children and their families.